PROFIL VEGETASI DATARAN RENDAH KOTA SEMARANG - Nana Kariada Tri Martuti; Margareta Rahayuningsih; Satya Budi Nugraha; Wahid Akhsin Budi Nur Sidiq (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2020)
Indonesia is known to the world as a mega biodiversity country because it has vibrantbiodiversity. Semarang has a unique topography starting from the beaches in thecoastal areas, lowlands to hills in the southern region. The different landscapes affectthe biodiversity in Semarang City. This study aims to analyze the distribution of vegetation and create a vegetation profile of Semarang. The results showed that each species' dominant pattern in each growth rate was relatively spread. The ability to controleach species in the community was relatively balanced. The sustainability of speciesdiversity could be maintained. Besides, it is necessary to manage and preserve vegetation types that are quite dominant and have beneficial values in terms of economy,ecology, and even socio-culture in Semarang. They can become a characteristic ofSemarang as the capital of Central Java.